PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Safitri, Shofi Yulia; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of Capital Structure, Liquidity, and Leverage on Firm Value with Profit Growth as an Intervening Variable in Retail Companies Listed on the Indonesia Stock Exchange during the period 2019-2022. The population in this study consists of all retail companies listed on the Indonesia Stock Exchange (IDX), totaling 32 companies. The sampling technique used in this research is purposive sampling, resulting in 9 samples. Data analysis and hypothesis testing in this study utilize the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The hypothesis testing results of direct and indirect effects using Smart PLS 3.0 indicate that The Capital Structure does not significantly influence Profit Growth. Liquidity does not significantly influence Profit Growth. Leverage does not significantly influence Profit Growth. Capital Structure has a positive and significant influence on Firm Value. Liquidity does not significantly influence Firm Value. Leverage does not significantly influence Firm Value. The results of indirect effect hypothesis testing show that Capital Structure does not significantly influence Firm Value through Profit Growth. Liquidity does not significantly influence Firm Value through Profit Growth. Leverage does not significantly influence Firm Value through Profit Growth.